Online child sexual abuse: a convergent parallel mixed-method exploration among Bangladeshi youth - M Atiqul Haque; Marium Salwa; Md Redwanul Islam; Mohammad Ibrahim Ibne Towhid; Anika Tasnim; Md Maruf Haque Khan (BMJ Open)
Objectives This study aimed to explore the experience of online sexual abuse among school-going Bangladeshi youth.Design A convergent parallel mixed-method study. The quantitative strand employed a self-administered questionnaire survey conducted in classroom settings, while the qualitative strand used in-depth interviews guided by semistructured protocols. Data from both strands were analysed separately and then merged.Participants and settings Grade 9–10 students from four randomly selected schools in both an urban and a rural area of Bangladesh participated in the study. A total of 456 students participated in the quantitative survey, and 16 were subsequently interviewed for qualitative data.Outcome measures The frequency of online sexual abuse along with its contributing factors and patterns, including victim’s characteristics, perpetrator’s identity, potential avenue of abuse, knowledge and psychosocial consequences.Results About 88% of the participants reported using the Internet, and nearly 53% reported being victims of online sexual abuse at some point in their lives. The occurrence of common sexual abuses included online grooming (53%), cyberflashing (38%), sexting (35%), sexual solicitation (18%) and sextortion (12%) among Internet users. The odds of being sexually abused online were higher among urban children (OR=2.04, 95% CI 1.21–3.45), who spent more hours daily on the Internet (OR=1.09, 95% CI 1.01–1.18), who visited more social media (OR=1.42, 95% CI 1.27–1.59) and who used more Internet devices (OR=1.93, 95% CI 1.25–2.98). Many participants were aware of these incidents but did not know how to respond to online sexual abuse. Social media, chat groups and video games were described as primary avenues for abuse, while unemployed male young adults and partners in love affairs were identified as the possible perpetrators. Psychosocial consequences such as anxiety, depression, helplessness, stress, distrust, lack of concentration, social isolation, self-hate and suicidal attempts were reported by the victims. Encountering online sexual abuse also manifested in academic underperformance.Conclusion Urgent multisectoral measures are needed to address online sexual abuse to safeguard children’s right to be protected on online platforms.